Identification of marker genes associated with oxidative stress in hypertrophic cardiomyopathy using bioinformatics analysis and experimental validation - Jian Zhuo; Ding Ding; Mengkang Fan; Weiwei Lu; Xiaochen Lu; Lihong Yao; Hongzhuan Sheng (Scientific Reports)
Abstract Hypertrophic cardiomyopathy (HCM) is a common inherited cardiomyopathy, and the mechanisms by which oxidative stress contributes to HCM remain unclear. This study aimed to identify HCM-associated oxidative stress genes and evaluate their significance in HCM pathogenesis through bioinformatic analysis of public datasets. GSE36961 and GSE141910 were downloaded from the Gene expression Omnibus (GEO) database, and genes associated with oxidative stress were searched in the Gene Ontology (GO) database. After differential analysis, marker genes were obtained using LASSO and SVM-RFE algorithms. DAVID was used, along with the GSVA and GSEA packages to perform gene ontology, pathway function enrichment, and gene set enrichment analyses. CIBERSORT was used to analyze immune cell infiltration. Subsequently, validation of these genes was performed using the GSE141910 dataset. Finally, we validated gene expression and levels of oxidative stress in cellular models. In total, 33 OS-DEGs related to HCM were identified. These were closely related to apoptosis and immune response. Subsequently, seven marker genes from OS-DEGs were identified: JAK2, EDNRA, KCNA5, DNAJC15, CA3, PRKCD and KLF2. The functional enrichment analysis suggested that these markers may play corresponding roles in HCM by regulating oxidative stress, immune responses, cytokine interactions, and multiple other processes. In addition, according to CIBERSORT analysis, PRKCD and EDNRA may have an effect on the immune microenvironment of HCM patients. In vitro studies using neonatal rat cardiomyocytes showed increased ROS production and caspase activation, suggesting elevated oxidative stress and apoptosis in HCM. This study identified 7 oxidative stress-related genes in HCM, and deeply analyzed the function and regulation of the marker genes. At the same time, we also proposed that oxidative stress participate in HCM through apoptosis.